THE ROLE OF COMPETENCE IN DRIVING BUSINESS FORWARD: BIBLIOMETRIC ANALYSIS USING SCOPUS DATABASE - Harva, Zahra Berlianda; Rahmawan , Muhammad Diandra; Susanty , Ade Irma (PT. Jurnal Center Indonesia Publisher, 2025)
This This study aims to explore and analyze research trends related to competence in business, particularly within the context of small and medium-sized enterprises (SMEs), using a bibliometric approach. Data was extracted from the Scopus database and visualized using VOSViewer, facilitating the identification of key research clusters, influential authors, and the relationships between various keywords within the domain. The findings reveal significant clusters centered around